The witness - Roberts, Nora. (New York : G.P. Putnam's Sons, 2012)
"Daughter of a cold, controlling mother and an anonymous donor, studious, obedient Elizabeth Fitch finally let loose one night, drinking too much at a nightclub and allowing a strange man's seductive Russian accent to lure her to a house on Lake Shore Drive. The events that followed changed her life forever. Twelve years later, the woman now known as Abigail Lowery lives alone on the outskirts of a small town in the Ozarks. A freelance programmer, she works at home designing sophisticated security systems. Her own security is supplemented by a fierce dog and an assortment of firearms. She keeps to herself, saying little, revealing nothing. Unfortunately, that seems to be the quickest way to get attention in a tiny southern town. The mystery of Abigail Lowery intrigues local police chief Brooks Gleason, on both a personal and a professional level. He suspects that Abigail needs protection from something. Gleason is about to walk into the sights of very powerful and dangerous men. And Abigail, who has built a life based on security and self-control, is at risk of losing both."--Jacket p. [2].
Keywords: Child witnesses -- Fiction; Mafia -- Fiction; Murder -- Investigation -- Fiction; Police chiefs -- Arkansas -- Fiction; Arkansas -- Fiction; Romantic suspense fiction